Effects of organic and inorganic compounds of diesel exhaust particles on the mucociliary epithelium: An experimental study on the frog palate preparation - Trindade, Sergio Henrique Kiemle [UNESP]; Seriani, Robson; Lorenzi-Filho, Geraldo; de Mello Júnior, João Ferreira; Sennes, Luiz Ubirajara; Saldiva, Paulo Hilário Nascimento; Macchione, Mariângela (Elsevier, 2018)
The toxic actions of acute exposition to different diesel exhaust particles (DEPA) fractions on the mucociliary epithelium are not yet fully understood due to different concentrations of organic and inorganic elements. These chemicals elements produce damage to the respiratory epithelium and exacerbate pre-existent diseases. In our study we showed these differences in two experimental studies. Study I (dose-response curve - DRCS): Forty frog-palates were exposed to the following dilutions: frog ringer, intact DEPA diluted in frog-ringer at 3 mg/L, 6 mg/L and 12 mg/L. Study II (DEPF) (DEPA fractions diluted at 12 mg/L): Fifty palates - Frog ringer, intact DEPA, DEPA treated with hexane, nitric acid and methanol. Variables analyzed: relative time of mucociliary transport (MCT), ciliary beating frequency (CBF) and morphometric analysis for mucin profile (neutral/acid) and vacuolization. The Results of DRCS: Group DEPA-12 mg/L presented a significant increase in the MCT (p<0.05), proportional volume of acid mucus (p<0.05) and decreased proportional volume of neutral mucus and vacuoles (p<0.05). In relation of DEPF: A significant increase in the MCT associated to a decrease in the proportional volume of neutral mucus was founded in nitric acid group. In addition, a significant increase in the proportional volume of acid mucus was found in methanol group. We concluded that: 1) Increasing concentrations of intact DEPA can progressively increase MCT and promote an acidification of intra-epithelial mucins associated to a depletion of neutral mucus. 2) Intact DEPA seem to act as secretagogue substance, promoting mucus extrusion and consequently reducing epithelial thickness. 3) Organic fraction of low polarity seems to play a pivotal role on the acute toxicity to the mucociliary epithelium, by promoting a significant increase in the MCT associated to changes in the chemical profile of the intracellular mucins.
Keywords: Air pollution; Cilia; Epithelium; Particulate matter; Vehicle emissions